New DVB‐S2X constellations for improved performance on the satellite channel. (14th September 2015) - Eroz, Mustafa; Lee, Lin‐Nan; Loghin, Nabil; De Bie, Ulrik; Simoens, Frederik; Delaruelle, Daniel
Summary: Digital Video Broadcasting via satellite second generation has experienced worldwide adoption because of its revolutionary and yet practical physical layer technology and its flexibility. Recently, the standard has been updated with several new features without changing its fundamental structure. This paper provides a high‐level discussion on several of the most important additions to the new standard with particular emphasis on some of the new signal constellations. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This paper provides a high‐level description for the most important improvements provided by the newly updated Digital Video Broadcasting via satellite second generation part II standard. In particular, some of the new constellations along with theoretical and practical justifications for their choice are described. An efficient method of extending the physical layer signaling code is provided without affecting the signaling of the legacy modulation/coding pairs.